Revisiting insurance capital structure, risk-taking behaviour and performance between 1995 – 2002 - Akpan, Sunday Sunday; Mahat, Fauziah; Amin Noordin, Bany Ariffin; Md Nassir, Annuar (Canadian Center of Science and Education, 2017)
This paper examines the effect of capital structure and the moderation effect of risk-taking behaviour of insurance firms on performance of insurers in Nigeria from 1995 to 2002. This study became necessary as literatures in this area and regime are scarce. Secondary data from financial reports of each insurance firm were used. Descriptive statistics were used to describe the characteristics of the data while a two-stage estimation procedure of the fixed effect and random effect models were used to test the hypothetical framework of the study. Result shows that insurance capital structure (measured by equity ratio) had an insignificant negative effect on insurance performance while it had a significant positive effect on insurance performance if measured by technical provision ratios. On average, risk taking behaviour moderates the relationship between technical provision ratio and insurance performance. This study focused on capital structure and moderation effect of risk on performance of insurers in non risk-based capital era. Further study on risk-based capital era will provide more on performance of insurers before and after the implementation of risk-base capital requirement. These findings provide important insight to managers and regulators and investors by fostering more understanding of how to manipulate insurance capital and which source of fund should be used to embark on risky investment to attain superior performance. This investigation adds to literature on insurance capital structure, regulation and risk management and insurance performance in Nigeria.